Intercellular communication in the cumulus–oocyte complex during folliculogenesis: A review - Xie, Jun; Xu, Xiao; Liu, Suying (Frontiers in Cell and Developmental Biology, 2023)
During folliculogenesis, the oocyte and surrounding cumulus cells form an ensemble called the cumulus-oocyte complex (COC). Due to their interdependence, research on the COC has been a hot issue in the past few decades. A growing body of literature has revealed that intercellular communication is critical in determining oocyte quality and ovulation. This review provides an update on the current knowledge of COC intercellular communication, morphology, and functions. Transzonal projections (TZPs) and gap junctions are the most described structures of the COC. They provide basic metabolic and nutrient support, and abundant molecules for signaling pathways and regulations. Oocyte-secreted factors (OSFs) such as growth differentiation factor 9 and bone morphogenetic protein 15 have been linked with follicular homeostasis, suggesting that the communications are bidirectional. Using advanced techniques, new evidence has highlighted the existence of other structures that participate in intercellular communication. Extracellular vesicles can carry transcripts and signaling molecules. Microvilli on the oocyte can induce the formation of TZPs and secrete OSFs. Cell membrane fusion between the oocyte and cumulus cells can lead to sharing of cytoplasm, in a way making the COC a true whole. These findings give us new insights into related reproductive diseases like polycystic ovary syndrome and primary ovarian insufficiency and how to improve the outcomes of assisted reproduction.